Mineralogisk och mineralkemisk jämförelse mellan Rakkurijoki, Rakkurijärvi och förekomst av Discovery Zone FeOx, Kiruna Sverige - van der Stijl, Ivar (2014)
The investigated deposits, Rakkurijoki, Rakkurijarvi and Discovery Zone, are all located 6-8 km south-southwest of the currently mined Kiirunavaara AIO-deposit. Previous research in the three deposits has been very limited, where the most recent study focused on the Discovery Zone deposit. The main aim of this study was to compare the three deposits by studying the mineralization petrographically, combined with a compositional characterization using electron microprobe analysis (E.M.P.A.), the trace and minor element composition of oxides, sulphides, and classification of the silicates, and addressing the chemical environment of the deposits.Whole-rock geochemistry indicates that the setting of the sediments in Rakkurijoki is from an active continental margin and the meta-sediments are classified as arkose /lithoarenite. Whole-rock geochemistry from samples originating from Discovery Zone is inadequate to use for classification as metasomatism may have altered the primary composition of the whole-rock. The trace element compositions in the three studied deposits show distinct differences, especially with regards to the Al2O3 content, where samples from Rakkurijoki contain overall higher concentrations compared to Rakkurijärvi and Discovery Zone. Magnetite samples from the Rakkurijoki deposit shows analogous tendencies regarding the element concentrations with the average skarn deposits. Furthermore, Rakkurijärvi shows similar average concentrations of Ti and V as Rakkurijoki and the average skarn deposits, but lower concentrations of Al and Mn. Discovery Zone shows slightly greater average concentrations of V compared with the average IOCG-style deposits, but contains significantly less Al, Mn, and Ti. The author suggest that the low concentrations of trace elements in oxides from Discovery Zone could be explained by that there was an initial oxidation followed by subsequent reduction so that the primary Mn- , Ti-. and Al-bearing magnetite has been recrystallized to form secondary magnetite with low Mn, Ti and ...